Analisis Efektivitas Dana Zakat dalam Peningkatan Pendapatan Usaha Mustahik di Kabupaten Padang Lawas - Jogina Santi Siregar; Delima Sari Lubis; Rini Hayati Lubis (Journal of Islamic Social Finance Management, 2021)
ABSTRACT BAZNAS Padang Lawas Regency has distributed productive zakat funds to mustahiq and utilized zakat for business capital, but productive zakat funds have not been effective in increasing mustahiq's business income. This study aims to determine how the distribution of productive zakat funds, the utilization of productive zakat funds and the effectiveness of zakat funds in increasing mustahiq business income in Padang Lawas Regency. This study uses a descriptive qualitative approach with field research (field research). The results of this study indicate that economic development in increasing mustahiq business income in Padang Lawas Regency has not been effective in its implementation, from the four indicators used, namely targeting accuracy, program socialization, program monitoring and program objectives. Only indicators of target accuracy have been effective. This is due to poor monitoring from BAZNAS and non-existent assistance, lack of human resources, lack of mustahiq knowledge about zakat utilization and mustahik's lack of responsibility in managing their business after being given productive zakat funds. Keywords : Productive Zakat, Effectiveness, Mustahiq ABSTRAK BAZNAS Kabupaten Padang Lawas sudah menyalurkan dana zakat produktif kepada mustahik dan mendayagunakan zakat untuk modal usaha namun dana zakat produktif belum efektif dalam peningkatan pendapatan usaha mustahik. Penelitian ini bertujuan untuk mengetahui bagaimana penyaluran dana zakat produktif, pendayagunaan dana zakat produktif dan efektivitas dana zakat dalam peningkatan pendapatan usaha mustahik di Kabupaten Padang Lawas. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan penelitian lapangan (field Reseach). Hasil penelitian ini menunjukkan pengembangan ekonomi dalam peningkatan pendapatan usaha mustahik di Kabupaten Padang Lawas dalam pelaksanaannya belum efektif, dari empat indikator yang digunakan yaitu ketepatan sasaran, sosialisasi program, pemantauan program dan tujuan program. Hanya indikator ketepatan sasaran yang sudah efektif. Hal ini disebabkan pemantauan dari pihak BAZNAS yang kurang lancar serta pendampingan yang tidak ada, sumber daya manusia yang kurang, pengetahuan mustahik yang kurang tentang pemanfaatan zakat dan kurangnya tanggung jawab mustahik dalam mengelola usahanya setelah diberikan dana zakat produktif. Kata Kunci : Zakat Produktif, Efektivitas, Mustahik